Balancing Ecological and Anthropogenic Demands through Land Carrying Capacity Assessment in Tiworo Watershed - Lukman Yunus; La Baco Sudia; La Gandri; La Ode Muhammad Erif; Vivi Fitriani (PERTETA, 2025)
The Tiworo Watershed on Muna Island, Southeast Sulawesi, is experiencing significant ecological and anthropogenic pressures that threaten the sustainability of its ecosystem functions. Land cover changes have led to increased surface runoff and have impacted coastal ecosystems. This study aims to evaluate the carrying capacity of the Tiworo watershed by analyzing three key parameters: percentage of critical land (PCL), percentage of vegetation cover (PVC), and erosion index (EI), referring to the Minister of Forestry Regulation No. P.61/Menhut-II/2014. The research methods included spatial analysis based on Geographic Information Systems (GIS), collection of secondary data from satellite imagery and relevant agencies, and weighted calculations to determine land carrying capacity scores. The results revealed that 65.4% of the Tiworo watershed area is classified as potentially critical, with 8.14% falling into the critical to very critical category, mainly due to land use change and anthropogenic activities. Although vegetation cover is still relatively good (89.57%), the expansion of settlements and open land has the potential to disrupt ecological stability. The erosion index reached 13.65, far exceeding the tolerance threshold (ETOL 27.55 tons/ha/year), with 52.04% of the area experiencing very severe erosion (>480 tons/ha/year). The land carrying capacity score of 87.5 (good category) indicates that ecological capacity is still adequate, but high degradation pressure requires immediate intervention.